Makerspaces as educational spaces for innovation and entrepreneurship development - Castro, May Portuguez; Zermeño, Marcela Georgina Gómez (Zenodo, 2019)
this qualitative research seeks to describe how makerspaces promote open innovation and the development of entrepreneurship. these educational spaces have arisen to develop projects mediated by technology and have become as training centers that promote collaboration networks. to analyze how this interaction is carried out and determine the skills developed in these spaces, a case study was made with participants from two makerspaces located in the city of monterrey, mexico. the development of interviews and participant observations in these environments allowed determining how these spaces favor the development of entrepreneurship skills and how the participants use the available resources to generate innovative and creative ideas. these ideas will subsequently become enterprises, but entrepreneurs require an impulse from other actors in the entrepreneurial ecosystem to reach greater potential. findings show that the factors presented in the makerspaces are the following domains of analysis: characteristics of the models to which the entrepreneurs have access, the profile of the participants and their relationships, the types of training they receive, the skills developed by the entrepreneur, the entrepreneurial ecosystem and the available resources. : {"references": ["anderson, C. (2013). maKErS: la nueva revoluci\u00f3n industrial. Barcelona, Espa\u00f1a: Empresa activa. anderson, C. (2016). the maker movement: tangible goods emerge from ones and zeros. wired. (https://www.wired.com/2013/04/makermovement/) Benkler, y. (2015). la riqueza de las redes. Barcelona: Icaria Editorial. Browder, r.; aldrich, H.; Bradley, S. (2019). the emergence of the maker movement: Implications for entrepreneurship research. Journal of Business venturing, 34(3),459-476. Cankar, S.; Cankar, f. (2013). Innovation Can Be learned. In proceedings of the annual International Conference of the Bulgarian Comparative Education Society (pp. 145-150). Casta\u00f1o, C.; garay, u.; themistokleous, S. (2018). de la revoluci\u00f3n del software a la del hardware en educaci\u00f3n superior. rIEd. revista Iberoamericana de Educaci\u00f3n a distancia, 21(1), 135-153. doi: 10.5944/ried.21.1.18823 dougherty, d. (2013). the maker movement. Innovations technology. mIt press Journals, 7(3), 11-14. dougherty, d. (2016). free to make: How the maker movement is changing our schools, our jobs, and our minds. Berkeley, Ca: north atlantic Books. garc\u00eda, J.; garc\u00eda, f. (2015). artesan\u00eda digital y modernidad educativa. Education in the Knowledge Society (EKS), 16(1), 13-31. doi: 10.14201/eks20151611331 gershenfeld, n. (2012). How to make almost anything: the digital fabrication revolution. foreign affairs, 91, 43-57. gonz\u00e1lez, J.; Estebanell, m.; peracaula, m. (2018). \u00bfrobots o programaci\u00f3n? El concepto de pensamiento computacional y los futuros maestros. Education In the Knowledge Society (EKS), 19(2), 29-45. doi: 10.14201/eks20181922945 Harper anderson, E. (2018). Intersections of partnership and leadership in Entrepreneurial Ecosystems: Comparing three u.S. regions. Economic development Quarterly, 32(2), 119-134. Hatch, m. (2014). the maker manifesto: rules for innovation in the new world of crafters, hackers and tinkerers. new york: mcgrawHill. Hui, J.; gerber E. (2017), developing makerspaces as Sites of Entrepreneurship. In proceedings of the 2017 aCm Conference on Computer Supported Cooperative work and Social Computing (pp. 2023-2038). Husted, S.; rodr\u00edguez, g. o.; \u00c1lvarez, m. p. (2017). digitlab: tecnolog\u00edas emergentes y ambientes de aprendizaje mediado por tecnolog\u00edas para fortalecer habilidades de pensamiento y comunicaci\u00f3n en las disciplinas del dise\u00f1o. \u00c1mbitos: revista Internacional de Comunicaci\u00f3n, 35, 1-15. lindtner, S. (2015). Hacking with chinese characteristics: the promises of the maker movement against China's manufacturing culture. Science, technology & Human values, 40(5), 854-879. llisterri, J. J.; gligo, n.; Homs, o.; ru\u00edz-devesa, d. (2014). Educaci\u00f3n t\u00e9cnica y formaci\u00f3n profesional en am\u00e9rica latina. El reto de la productividad. Serie pol\u00edticas p\u00fablicas y transformaci\u00f3n productiva, 13. Caracas: Caf. (http://scioteca.caf.com/handle/123456789/378) maxwell, J. a. (2012). Qualitative research design: an Interactive approach. California: SagE publications, Inc. miranda, J.; Chavarr\u00eda-Barrientos, d.; ram\u00edrez-Cadena, m.; mac\u00edas, m. E.; ponce, p.; noguez, J.; wright, p.; molina, a.; p\u00e9rezrodr\u00edguez, r. (2017). open innovation laboratory for rapid realization of sensing, smart and sustainable products (S3 products) for higher education. International Scholarly and Scientific research & Innovation, 11(5), 1206-121"]}